Modified Fokker-Planck Acceleration for Forward-Peaked Transport Problems in Slab Geometry. Issue 5 (29th July 2021) - Kuczek, J.J.; Patel, J.K.; Vasques, R.
Abstract: This paper introduces a new acceleration technique for the convergence of the solution of transport problems with highly forward-peaked scattering. The technique is similar to a conventional high-order/low-order (HOLO) acceleration scheme. The Fokker-Planck equation, which is an asymptotic limit of the transport equation in highly forward-peaked settings, is modified and used for acceleration; this modified equation preserves the angular flux and moments of the (high-order) transport equation. We present numerical results using the Screened Rutherford, Exponential, and Henyey–Greenstein scattering kernels and compare them to established acceleration methods such as diffusion synthetic acceleration (DSA). We observe three to four orders of magnitude speed-up in wall-clock time compared to DSA.